Pendampingan Kegiatan Ektrakulikuler Drumband dalam Meningkatkan kompetensi Non-akademik Peserta Didik SMPN 1 Kota Pariaman - Apriliani, Wilda; Kustati, Martin; Amelia, Rezki; Gusmirawati, Gusmirawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This mentoring aims to see the implementation of Drumband Extracurricular activities towards improving non-academic competencies of students at SMPN 1 Pariaman. Drumband Extracurricular Activities at SMPN 1 Pariaman focus on the technical aspects of playing music, training students to master musical instruments such as snare drums, bass drums, tom-toms, pianicas, and cymbals. Practices are carried out routinely to prepare them to perform at school events and competitions. However, this activity emphasizes individual and team musical abilities without linking them to social activities or community service. Although students are skilled, they do not have structured opportunities to apply social roles through music, and the emphasis is more on technical achievements than on developing social character. This mentoring uses the Service Learning method. The results of the mentoring show that student involvement in Drumband Extracurricular activities provides a positive contribution to the development of soft skills, such as discipline, teamwork, creativity, and self-confidence. Thus, Drumband activities not only provide technical musical skills, but also improve non-academic competencies that are important for student development.